Lithium-ion batteries enabled by silicon anodes - Ban, Chunmei; Xu, Kang (IET energy engineering series, 2021)
Deploying lithium-ion batteries depends on cost-effective materials with high energy and power density to facilitate lower weight. Si-based anode materials offer superior storage capacity. This reference presents current knowledge about the use of silicon and its derivates for Li-ion batteries.